Probabilistic assessment of the cumulative risk from dietary heavy metal exposure in Chongqing, China using a hazard-driven approach - Jiahui Chen; Jingrong Chen; Mintao Li; Ping Feng; Mei Qin; Ting Chen; Shuquan Luo; Jian Zhao; Xiaofeng Yan; Jinyao Chen; Xuemei Lian; Huadong Zhang; et al. (Scientific Reports)
Abstract Cumulative risk assessment is significant for evaluating the combined exposure to multiple substances, but its widespread acceptance and application have been limited due to the complexity of clarifying and assessing actual exposure. In this study, we conducted a cumulative risk assessment based on hazard-driven criteria to evaluate the co-exposure to elemental contaminants in the diet of the population in Chongqing Municipality. The cumulative risk was calculated and evaluated using Monte Carlo modeling and the modified Reference Point Index (mRPI) method. Neurotoxicity and nephrotoxicity were identified as the main toxic endpoints, and the final evaluation elements included were Pb, Cd, As, and Hg. The results showed that the combined mRPI values for neurotoxicity and nephrotoxicity, resulting from exposure to the four heavy metals, ranged from 0.922 to 4.835 and 1.306 to 7.031, respectively. Cd and Pb were the primary contributors to nephrotoxicity, while Pb was the main contributor to neurotoxicity. The results indicated that combined dietary exposure to Pb, Cd, As, and Hg may pose risks of neurotoxicity and nephrotoxicity, with the combined exposure likely amplifying this risk compared to exposure to individual heavy metal elements. mRPI proves to be a more suitable index for cumulative risk assessment using a hazard-driven approach compared to other indexes, as it is derived based on specific studies and endpoints.